ANCIENT ROMAN URINE CHEMISTRY. Issue 1 (December 2016) - Witty, Michael
ABSTRACT: Important ancient Roman chemical processes involved ammonium, especially fulling. Ammonium accumulates in decaying urine as a dilute chemical agent but is unfortunately present alongside substances which interfere with later processes, such as malodorous organic compounds and bacterial debris. This paper demonstrates how ancients may have obtained concentrated material by crystallization of ammonium salts and purification to a high degree by simple decanting, which uses only those resources available in the first century AD. It is proposed that first century Romans used decayed urine to produce the urine powder "Struvite", a pure and concentrated form of ammonium. Possession of concentrated ammonium allows for a very wide range of chemical processes but only the very simplest example is presented in this paper; smelling salts.